Pemanfaatan Buah Patikala (Etlingera Elatior) Terhadap Kualitas Mikrobiologi Daging Ayam Afkir - Oktavia, Nanda Dwi; Majid, Irmawaty; Mutmainna, Andi (Universitas Islam Negeri Alauddin Makassar, 2024)
Patikala fruit is a local Indonesian plant that contains many secondary metabolite compounds wich can fungtion as anti bacterials. The aim of this research is to determine the use of patikala fruit (Etlingera elatior) on microbes in rejected chicken meat. The treatments in this study were P0 without treatment, P1 storege time 3 hours, P2 storage time 4 hours and P3 storage time 5 hours. The parameters measured in this research are the microbiological quality of rejected chicken meat which includes testing for Total Plate Count (TPC), Coliform, and E. coli. The resut of the research showed thet the the used of patikala fruit ekstrak (Etlingera elatior) on the microbial quality of rejected chicken meat did not have a significant effect on the Total Plate Count (TPC) test, Colliform test and E. coli test. However based on the data, patikala fruit ekstrak (Etlingera elatior) could inhibit the growth of mikroba samples of rejected chicken meat